Large-Plate Method for the Assay of Neomycin in Serum - Van Soestbergen, A. A. (1969)
A large-plate method employing radial diffusion from small paper discs for assaying serum levels of neomycin is described. More than 120 discs placed on a loading plate and loaded with 20 μliters of sample could all be brought into contact with the agar plate at one time. The requirement for elaborate statistical design to compensate for time-dependent bias was thus eliminated. The dose-response curve was linear for a range of at least 0.5 to 2.5 μg/ml. The experimental limits for the actual zone width (distance from the edge of the paper disc to the outer edge of the inhibition zone) for 120 repetitions of the assay of neomycin in one and the same serum, carried out simultaneously on one large plate, were about ± 6% (95% confidence interval). The 95% confidence interval for the distribution of difference between duplicate zones obtained for the assay of neomycin in 34 different sera, also carried out on one plate, was about ± 10%. The dose-response lines for a standard and for three unknown sera, when carried out together on one plate, were parallel within the variability (± SD one) of the zone width. The large-plate method is considered to be more efficient than the use of the smaller petri dishes. The method is suitable for the assay of penicillin in serum and can most probably be used for the assay of a wide variety of substances for which radial diffusion from paper discs into agar is feasible.